Pemantauan Kesesuaian Kualitas Air pada Kolam Pembesaran Ikan Nila (Oreochromis niloticus) di Pokdakan Lestari, Klangenan, Cirebon - Hidayaturohman, Fajar; Mollynda, Meutia; Elinah, (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Tilapia (Oreochromis niloticus) farming is one of the freshwater fishery commodities that has high economic value and has the potential for sustainable development. The success of tilapia farming is largely determined by the quality of water as the main living medium. This study aims to monitor the suitability of water quality in tilapia (Oreochromis niloticus) grow-out ponds at Pokdakan Lestari, Klangenan Village, Cirebon Regency. The parameters observed include temperature, pH, dissolved oxygen (DO), and brightness. Measurements were taken in situ using a Water Quality Checker (WQC) and Secchi disk in the morning, afternoon, and evening for 14 days, and the results were analyzed descriptively and comparatively with reference to the SNI 7550:2009 standard. The results showed that the water temperature ranged from 25.6 to 31.3°C with an average of 28.2°C; pH ranged from 6.6 to 8.3 with an average of 7.3; DO ranged from 3.52 to 6.26 mg/L with an average of 4.93 mg/L; and brightness ranged from 30 to 40 cm with an average of 34.6 cm. Overall, the water quality parameters were still within the SNI standard range, although the DO value was close to the critical limit. Thus, the water quality conditions of the grow-out ponds were still suitable for supporting tilapia growth, but regular water quality monitoring was still required to maintain the stability of the aquaculture ecosystem.